High-performance PCR composite material and preparation method thereof

By blending PCR return material with polyethylene, and modifying thermoplastic polyurethane elastomer and -2-hydroxyethyl methacrylate using solid-phase grafting method and surface plasma activation technology, the problem of insufficient mechanical properties of PCR return material was solved, and the preparation of high-performance PCR composite materials was achieved, with significant mechanical properties and aging resistance improvement.

CN119591973APending Publication Date: 2025-03-11TIANJIN RUIJIE PLASTIC PROD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411399407.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The mechanical properties of existing PCR return materials are insufficient and are prone to doping impurities and contaminants, affecting the overall performance of the material and product quality.

Method used

The preparation method of high-performance PCR composite materials is adopted, including blending PCR return material and polyethylene, and modifying thermoplastic polyurethane elastomer and -2-hydroxyethyl methacrylate through solid-phase grafting method and surface plasma activation technology to form a modified blend and a modified HEMA-g-TPU, and then processed into high-performance PCR composite particles in a twin-screw extruder.

Benefits of technology

It significantly improves the mechanical properties, heat resistance and wear resistance of PCR composite materials, enhances the adhesion and aging resistance of the material, and reduces the use of additives, reducing production costs and pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and relates to a high-performance PCR composite material and a preparation method thereof, the high-performance PCR composite material comprises 10-20 parts of polyethylene, 0.1-0.5 part of an initiator, 0.1-0.5 part of a catalyst, 50-60 parts of a PCR return material, 10-20 parts of TPU, HEMA and 5-10 parts of an antioxidant. The preparation method comprises the following steps: (1) blending the PCR return material with polyethylene to obtain a blend; (2) mixing HEMA (hydroxyethyl methacrylate), TPU (thermoplastic polyurethane), an initiator and a catalyst, and reacting to obtain HEMA-g-TPU; the blend and HEMA-g-TPU are subjected to plasma activation, and a modified blend and modified HEMA-g-TPU are obtained; and (3) adding the modified blend and the modified HEMA-g-TPU into a twin-screw extruder, adding an antioxidant, and processing by the extruder to obtain the high-performance PCR composite material particles. The problem that the mechanical property of the PCR returned material is insufficient can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a high-performance PCR composite material and a preparation method thereof. Background Art

[0002] With the rapid development of modern science and technology and the continuous progress of human society, plastics have become an increasingly important part of people's daily lives, and the output of plastics has increased year by year. However, this has led to the generation of a large amount of waste plastics, which has not only caused serious pollution to the environment, but also caused a large amount of resource waste. Therefore, post-consumer recycled (PCR, Post Consumer Recycled) materials, that is, recycling and reusing waste plastics, can not only save costs, but also increase economic benefits, and has become a hot topic in the current industry's low-carbon research.

[0003] However, the quality of PCR recycled materials obtained by factories today is generally poor. On the one hand, the recycled materials have been repeatedly processed and heated, and the resin and additives have decomposed, resulting in a decrease in molecular weight and performance. On the other hand, the repeated processing process is prone to involve impurities (dust, metal debris, etc.) or other pollution (release agents, cleaning agents, anti-rust oil, paint, heavy metals, etc.). Directly mixing these recycled materials with new materials will inevitably have a negative impact on the material's mechanical, heat resistance, odor VOC, processing and other properties, thereby affecting the quality, reliability and life of the final product. Summary of the invention

[0004] In order to solve the defect of insufficient PCR return material mechanics in the prior art, the present invention provides a high-performance PCR composite material and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-performance PCR composite material, including 10 to 20 parts of polyethylene, 0.1 to 0.5 parts of initiator, 0.1 to 0.5 parts of catalyst, 50 to 60 parts of PCR recycled material, 10 to 20 parts of thermoplastic polyurethane elastomer, 10 to 20 parts of 2-hydroxyethyl methacrylate, and 5 to 10 parts of antioxidant.

[0006] Furthermore, the PCR recycled material is a blend of polypropylene recycled material PCR-PP and polyethylene recycled material PCR-PE.

[0007] Preferably, the mass ratio of PCR-PP to PCR-PE is 8:2.

[0008] Specifically, the initiator is selected from one or more of benzoyl peroxide (BPO), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), acrylamide (AM), 2,5-di-tert-butylperoxide-2,5-dimethyl-3-acetylene (LPO) and 1,3-di-tert-butylperoxide isopropylbenzene.

[0009] Specifically, the catalyst is selected from one or more of diisopropylbenzene peroxide (DCP), di-tert-butyl peroxide (DTBP) and diisopropylbenzene hydroperoxide.

[0010] Specifically, the antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 and antioxidant 1076.

[0011] The present invention also provides a method for preparing a high-performance PCR composite material, comprising the following steps: (1) blending PCR recycled material: blending PCR recycled material with polyethylene to obtain a blend;

[0012] (2) Modification: 2-hydroxyethyl methacrylate, thermoplastic polyurethane elastomer, initiator and catalyst are mixed and reacted to obtain HEMA-g-TPU; the blend and HEMA-g-TPU are plasma activated to obtain a modified blend and modified HEMA-g-TPU respectively;

[0013] The plasma activation conditions are as follows: radio frequency 13.65MHz, power 100-300W, working gas is at least one of oxygen, hydrogen, argon and nitrogen, and the flow rate of the working gas is 20-50cm 3 / min, process for 5 to 10 minutes;

[0014] (3) Granulation: Add the modified blend and modified HEMA-g-TPU into a twin-screw extruder, add an antioxidant, and process through the extruder to obtain high-performance PCR composite material particles.

[0015] Preferably, the PCR recycled material in step (1) is obtained by mixing PCR-PP and PCR-PE in a mass ratio of 8:2 and sieving.

[0016] Preferably, the reaction temperature in step (2) is 100-130° C., and the reaction time is 5-7 hours.

[0017] Preferably, the temperature of each section of the extruder is set at 180-220°C.

[0018] Beneficial effects: 1. The solid phase grafting method is used to graft and modify thermoplastic polyurethane elastomer with 2-hydroxyethyl methacrylate. The reaction temperature is low, the reaction device is widely used, and the post-treatment is simple. The reactive hydroxyl functional group is introduced while improving the performance of TPU. Compared with the grafted product prepared by the melt method, it has a better effect, reduces the use of additives in the production process, saves costs, and reduces pollution;

[0019] 2. Using surface plasma activation technology, different gases are ionized to obtain different functional groups. These plasma gases break the chemical bonds on the surface of polymer materials, change the chemical composition and structure of the material surface, replace the original chemical bonds with the required chemical groups, and achieve surface chemical and physical modification. An oxide layer is formed on the material surface and functional groups such as hydroxyl groups are introduced to achieve performance requirements such as improving material adhesion, enhancing wear resistance, and increasing thermal aging resistance.

[0020] 3. A large number of hydroxyl functional groups are introduced into the surface of PCR recycled materials and TPU, which have high polarity and can bond the components together. They can also bond other impurities in the PCR recycled materials, thereby improving the mechanical properties of the blended modified plastics and making them more wear-resistant and heat-resistant. The addition rate of PCR recycled materials is greatly increased without reducing the quality of the product, which is conducive to the recycling of recycled materials.

[0021] 4. The components also include polyethylene, which can be low molecular weight polyethylene. The polymer chain is short, the intramolecular structure is looser, and the force between the molecular chains is relatively weak. These structures make it fluid, easy to melt at high temperatures, and easy to detect reactions. Adding it to PCR recycled materials can enhance the mechanical strength of the recycled materials, allowing them to withstand higher temperatures, and can also improve flexibility, making them easier to mold;

[0022] In addition, after plasma modification, active groups are added to the surface of low molecular weight polyethylene, which will cross-link with HEMA-g-TPU to form TPU-PE-HEMA, which is beneficial to improving the performance of the material. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific implementation methods. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative changes belong to the protection scope of the present invention.

[0024] The present invention provides a high-performance PCR composite material, which actually uses PCR recycled material as raw material and specifically includes, by weight, 10 to 20 parts of polyethylene, 0.1 to 0.5 parts of initiator, 0.1 to 0.5 parts of catalyst, 50 to 60 parts of PCR recycled material, 10 to 20 parts of thermoplastic polyurethane elastomer (TPU), 10 to 20 parts of 2-hydroxyethyl methacrylate (HEMA), and 5 to 10 parts of antioxidant.

[0025] The PCR recycled material is a blend of polypropylene recycled material PCR-PP and polyethylene recycled material PCR-PE, and the mass ratio of PCR-PP to PCR-PE is 8:2.

[0026] The polyethylene may be one or more of LDPE or LLDPE.

[0027] Specifically, the initiator is selected from one or more of benzoyl peroxide (BPO), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), acrylamide (AM), 2,5-di-tert-butylperoxide-2,5-dimethyl-3-acetylene (LPO) and 1,3-di-tert-butylperoxide isopropylbenzene.

[0028] The catalyst is selected from one or more of diisopropylbenzene peroxide (DCP), di-tert-butyl peroxide (DTBP) and diisopropylbenzene hydroperoxide.

[0029] The antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 and antioxidant 1076.

[0030] The present invention also provides a method for preparing a high-performance PCR composite material, comprising the following steps: (1) PCR recycled material blending: mixing PCR recycled materials PCR-PP and PCR-PE at a mass ratio of 8:2, and blending with polyethylene to obtain a blend;

[0031] (2) Modification: 2-hydroxyethyl methacrylate, thermoplastic polyurethane elastomer, initiator and catalyst are mixed and reacted at 100-130°C for 5-7h, preferably at 120°C for 6h, and HEMA-g-TPU is obtained after washing and drying; the above blend and HEMA-g-TPU are plasma activated respectively, and the plasma activation conditions are set as radio frequency 13.65MHz, power 200W, working gas oxygen and nitrogen 1:1, and the flow rate of working gas is 30cm 3 / min, treated for 10min, and bombarded with high-energy ion beams using surface plasma activation technology to obtain modified blends and modified HEMA-g-TPU;

[0032] (3) Granulation: Add the modified blend and modified HEMA-g-TPU into a twin-screw extruder, add an antioxidant, control the screw speed at 250-300 r / min, and process through the extruder to obtain high-performance PCR composite material particles. The temperature of the twin-screw extruder feed section is 180°C, the temperature of the shear melting section is 210°C, the temperature of the mixing section is 210°C, and the temperature of the extrusion section is 220°C.

[0033] Example

[0034] According to the preferred method of the above preparation method, different component ratios are used for preparation to obtain different PCR composite materials, as shown in the following table.

[0035]

[0036] Comparative Example 1

[0037] The raw material ratio and preparation method in Example 1 are the same, except that the compatibilizer low molecular weight polyethylene is not added.

[0038] Comparative Example 2

[0039] The raw material ratio and preparation method in Example 1 are the same, except that HEMA is not added to graft-modify TPU.

[0040] Comparative Example 3

[0041] The raw material ratio and preparation method in Example 1 are the same, except that the blend (PCR recycled material and low molecular weight polyethylene) is not subjected to plasma activation modification.

[0042] Comparative Example 4

[0043] The raw material ratio and preparation method in Example 1 are the same, except that HEMA is not added to modify the TPU, and the blend (PCR recycled material and low molecular weight polyethylene) is not plasma modified.

[0044] Performance Testing

[0045] The composite material particles prepared in the above embodiments and comparative examples were injection molded by an injection molding machine to prepare standard test specimens. The temperatures of each section of the barrel were 215° C., 205° C., 200° C., and 200° C., and the injection pressure was 80 MPa.

[0046] The tensile strength and elongation at break were tested according to GB / T 1040.2-2006 standard, with a tensile speed of 50 mm / min; the flexural modulus and flexural strength were tested according to GB / T 9341-2008, with a flexural speed of 2 mm / min; the notched impact strength was tested according to GB / T 1843-2008, with the room temperature treatment process being 23°C for 24 hours; the heat aging test was conducted according to GB / T 7141, with a test temperature of 150°C and an aging time of 500 h; the wear resistance test was conducted according to GB / T 3960-2016 standard, with the wear resistance being measured in terms of volume wear, in units of mm 3 , the smaller the volume wear, the better the wear resistance.

[0047] The performance tests of Example 1 and Comparative Examples 1 to 4 are as follows:

[0048]

[0049] The performance tests of Examples 2 to 7 are as follows:

[0050]

[0051] From the above data, it can be seen that the addition of compatibilizer low molecular weight polyethylene can effectively improve the performance of the composite material. The tensile strength of the PCR composite material prepared by the present invention can reach up to 89.5MPa, the flexural strength can reach up to 95MPa, the elongation at break can reach up to 720%, and the notched impact strength can reach up to 77.2KJ / m2. It has good mechanical properties, and its heat aging is not brittle for more than 500h at 150°C, has excellent heat resistance and aging resistance, small wear resistance index, and excellent wear resistance. If low molecular weight polyethylene is not added (Comparative Example 1), the various properties of the obtained composite material are obviously reduced. It can be seen that it effectively improves the compatibility between materials and can improve the performance of the composite material; when the TPU and PCR recycled material blends are not modified (Comparative Example 4), it can be clearly seen that the mechanical properties, aging resistance and wear resistance of the obtained composite material are significantly reduced compared with the performance of the modified composite material. It can be seen that the modification of the two has a synergistic effect on enhancing the performance of the composite material. In addition, if only one of the TPU and PCR recycled material blends is modified (Comparative Examples 2 and 3), the polyethylene and TPU will basically not be able to copolymerize, and the two will be stratified from each other, so that the performance of the composite material cannot be significantly improved, especially if HEMA is not added to the TPU for grafting modification (Comparative Example 2), the reactive hydroxyl functional group cannot be introduced, and it is impossible for it to react with the matrix material to achieve the enhancement effect.

[0052] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of this application.

Claims

1. A high-performance PCR composite material, characterized in that: The invention comprises, by weight, 10 to 20 parts of polyethylene, 0.1 to 0.5 parts of initiator, 0.1 to 0.5 parts of catalyst, 50 to 60 parts of PCR recycled material, 10 to 20 parts of thermoplastic polyurethane elastomer, 10 to 20 parts of 2-hydroxyethyl methacrylate and 5 to 10 parts of antioxidant.

2. The high performance PCR composite material according to claim 1, characterized in that: The PCR recycled material is a blend of polypropylene recycled material PCR-PP and polyethylene recycled material PCR-PE.

3. The high performance PCR composite material according to claim 2, characterized in that: The mass ratio of PCR-PP to PCR-PE is 8:

2.

4. The high performance PCR composite material according to claim 1 or 2, characterized in that: The initiator is selected from one or more of benzoyl peroxide, 2,3-dimethyl 2,3-diphenylbutane, acrylamide, 2,5-di-tert-butylperoxide-2,5-dimethyl 3-acetylene and 1,3-di-tert-butylperoxide isopropylbenzene.

5. The high performance PCR composite material according to claim 1 or 2, characterized in that: The catalyst is selected from one or more of diisopropylbenzene peroxide, di-tert-butyl peroxide and diisopropylbenzene hydroperoxide.

6. The high performance PCR composite material according to claim 1 or 2, characterized in that: The antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 and antioxidant 1076.

7. The method for preparing a high-performance PCR composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) blending PCR recycled material: blending PCR recycled material with polyethylene to obtain a blend; (2) Modification: 2-hydroxyethyl methacrylate, thermoplastic polyurethane elastomer, initiator and catalyst are mixed and reacted to obtain HEMA-g-TPU; the blend and HEMA-g-TPU are plasma activated to obtain a modified blend and a modified HEMA-g-TPU respectively; (3) Granulation: Add the modified blend and modified HEMA-g-TPU into a twin-screw extruder, add an antioxidant, and process through the extruder to obtain high-performance PCR composite material particles.

8. The method for preparing a high-performance PCR composite material according to claim 7, characterized in that: The PCR recycled material described in step (1) is obtained by mixing PCR-PP and PCR-PE in a mass ratio of 8:2 and sieving.

9. The method for preparing a high-performance PCR composite material according to claim 7, characterized in that: The reaction temperature in step (2) is 100-130° C., and the reaction time is 5-7 hours.

10. The method for preparing a high-performance PCR composite material according to claim 7, characterized in that: The temperature of each section of the extruder is set at 180-220°C.

Citation Information

Patent Citations

  • Recycled high-density polyethylene modified material containing polypropylene and modifying method thereof

    CN102617907A

  • Waterproof moisture-permeable thermoplastic polyurethane polymer and production method thereof

    CN110760180A

  • Regenerated plastic pipe and preparation method thereof

    CN117903515A

  • Modified recycled polyethylene plastic for plastic pipeline and preparation method therefor

    WO2022088230A1